Symptom experience and their effects on health-related quality of life over time in adults with primary brain tumor receiving radiotherapy - Natthacha Chiannilkulchai (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The purpose of this prospective study was to evaluate patterns, relationships, and factors predicting changes in symptom experiences and adverse effects on health related quality of life (HRQOL) in adults with primary brain tumors (PBT) receiving radiotherapy, using the Symptom Management Model as a conceptual framework. One hundred and twenty adults aged above 18 years were recruited from three tertiary care hospitals. The measurements in this study comprised of the demographic and medical record form, the Mini- Mental State Examination, the M.D Anderson Symptom Inventory-Brain Tumor, and the Functional Assessment of Cancer Therapy-Brain. Data were collected prior to, during, and at the end of radiotherapy. Descriptive statistics, ANOVA, MANOVA, and GEE were used to analyze the data. The result showed that the majority of patients were meningiomas (60.0%) and pituitary adenoma (16.7%). Radiotherapy included Intensity-modulated radiotherapy (IMRT), X-knife a median fractional dose of 2.0 Gy (range 1.8-6.75) up to a median total dose of 45 Gy (range 20.0-70.0), and a Cyber knife with a median fractional dose of 4.63 Gy (range 4.0- 6.75 Gy) up to a mode total dose of 25 Gy (20.0-33.75 Gy). The pattern of symptom occurrence and severity increased in a linear pattern, whereas symptom interference changed in a quadratic pattern. The tumor type had a significant predicted symptom experience at each time point and over time. The type of radiotherapy significantly predicted symptom occurrence and severity during and at the end of treatment and over time. Tumor laterality significantly predicted symptom occurrence at the end of treatment and predicted the symptom severity over time. The interaction between tumor laterality and tumor type significantly predicted symptom occurrence and severity before receiving radiotherapy and predicted symptom occurrence over time. The interaction between tumor location and tumor type significantly predicted symptom severity during treatment and predicted both symptom severity and interference at the end of receiving radiotherapy. The pattern of HRQOL decreased after receiving radiotherapy 8-10 Gy, but it increased at the end of radiotherapy. The symptom severity and interference predicted HRQOL at each time point and over time. It is recommended that patients with PBT, receiving radiotherapy, should be monitored for their specific symptoms including weakness, sad feelings, irritability and difficulty with concentration from the beginning until the end of radiation therapy. Practice guidelines to manage these symptoms should be developed in order to better improve their quality of life across the treatment trajectory.